2019
DOI: 10.3389/frobt.2019.00101
|View full text |Cite
|
Sign up to set email alerts
|

A SWOT Analysis of the Field of Virtual Reality for Firefighter Training

Abstract: Virtual reality (VR) research has gone through rapid advances and the technology has established itself as a valuable training tool in many domains. While research in the field of emergency response, and more specifically in the field of firefighting, is still catching up, the future potential of VR technology for training is promising. This paper uses the SWOT framework to analyse the strengths, weaknesses, opportunities, and threats immersive VR technology faces in the field of firefighter training. While us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 108 publications
0
62
0
Order By: Relevance
“…Although there has been a lot of research on the adoption of AR for training, few studies have concentrated on the context of firefighting training [ 27 , 28 , 29 ], which mostly examined VR-based training systems. This research details the user experience of augmented reality in firefighting training, and provides a deeper understanding of the behavioral purpose to use augmented reality in marine training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although there has been a lot of research on the adoption of AR for training, few studies have concentrated on the context of firefighting training [ 27 , 28 , 29 ], which mostly examined VR-based training systems. This research details the user experience of augmented reality in firefighting training, and provides a deeper understanding of the behavioral purpose to use augmented reality in marine training.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To direct an evidence-based integration of VR in police training and related research, a SWOT analysis was conducted to identify the strengths, weaknesses, opportunities, and threats when applying VR in police training. While the SWOT framework was originally used as a tool to analyse market forces impacting the standing of companies, it has been utilized successfully in academia to analyse the application of emerging technologies in a specific field (e.g., Düking et al, 2018;Engelbrecht et al, 2019). A summary of the strengths, weaknesses, opportunities, and threats can be found in Figure 1.…”
Section: Virtual Reality: New Directions In Scenario-based Police Trainingmentioning
confidence: 99%
“…As such, it might be concluded that the most advanced, technologically immersive system possible should be designed to maximize user presence. Therefore, the immaturity of the technology and the resulting cybersickness are considered as weaknesses of VR training (Engelbrecht et al, 2019). Therefore, great developmental efforts have been put into improving frame-rate, tracking, field of view, refresh rate, latency, and resolution over the past years (Cummings and Bailenson, 2016).…”
Section: Artificial Environments -Real Emotions?mentioning
confidence: 99%
“…15 domain experts positively evaluated the system, despite low visual quality in this first prototype. A review of firefighting environments is provided by Engelbrecht et al [46].…”
Section: Training Environments Firefighter Training In Vrmentioning
confidence: 99%